THE ISSUE OF CONVICTS FORMER LAW ENFORCEMENT OFFICIALS IN THE CONTEXT OF CLASSIFICATION OF PRISONERS - Zilfimyan, David (State and Law, 2020)
The article is dedicated the issue of convicts-former law enforcement agencies in the context of the legislative provisions for the classification of persons sentenced to imprisonment and the theoretical approaches to the classification, purposes, criteria and significance. The classification of persons sentenced to imprisonment is not a mere institute of penal law. Its initial legal bases and criteria are set out in criminal law where many jurisdictions and legal institutions are directly linked to the classification of persons sentenced to imprisonment.
Keywords: the convicts from a former law enforcement officers, classification of convicted persons, separate maintenance of the convicts, standards prescribed by the law on the classification of persons sentenced to imprisonment, objectives of the classification of prisoners, ways of ensuring the security of persons sentenced to imprisonment